2022
DOI: 10.1177/09603271221093630
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOXC-AS3 overexpression inhibits TGF-β2-induced colorectal cancer cell migration and invasion by sponging miR-1269

Abstract: Objective Long non-coding RNA (lncRNA) HOXC-AS3 has been characterized as a cancer-related lncRNA in many types of cancer, while its role in colorectal cancer (CRC) is unknown. Methods The expression of HOXC-AS3 and TGF-β2 were detected by RT-qPCR. Overexpression assays were performed to explore the interaction between HOXC-AS3 and TGF-β2. A follow-up study was performed to explore the prognostic value of HOXC-AS3 for CRC. The direct interaction between HOXC-AS3 and miR-1269 was assessed with RNA-RNA pulldown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Interestingly, HOXC‑AS3 was significantly positively correlated with the well-known oncogenic lncRNA HOTAIR, but negatively correlated with HOXC10. 37 In a subsequent study by Zhang et al, 12 HOXC-AS3 was reported to be significantly downregulated in CRC tissues and CRC cell lines. The observed differences in HOXC-AS3 expression in CRC tissues may be attributed to the ethnicity of the individuals in these two studies.…”
Section: The Role Of Hoxc‑as3 and Its Regulatory Mechanisms In Variou...mentioning
confidence: 93%
See 4 more Smart Citations
“…Interestingly, HOXC‑AS3 was significantly positively correlated with the well-known oncogenic lncRNA HOTAIR, but negatively correlated with HOXC10. 37 In a subsequent study by Zhang et al, 12 HOXC-AS3 was reported to be significantly downregulated in CRC tissues and CRC cell lines. The observed differences in HOXC-AS3 expression in CRC tissues may be attributed to the ethnicity of the individuals in these two studies.…”
Section: The Role Of Hoxc‑as3 and Its Regulatory Mechanisms In Variou...mentioning
confidence: 93%
“…The observed differences in HOXC-AS3 expression in CRC tissues may be attributed to the ethnicity of the individuals in these two studies. Zhang et al 12 also found that low HOXC-AS3 levels were indicative of poor survival in CRC patients. Notably, HOXC-AS3 overexpression effectively impedes TGF-β2-induced migration and invasion in CR4 and RKO colorectal cancer cells by acting as a sponge for miR-1269.…”
Section: The Role Of Hoxc‑as3 and Its Regulatory Mechanisms In Variou...mentioning
confidence: 96%
See 3 more Smart Citations